Some benefits of reducing inflation in transition economies - Monika Blaszkiewicz; Jerzy Konieczny; Anna Myslinska; Artur Radziwil; Wozniak Przemyslaw (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
We analyse welfare effects of the interactions between the tax system and inflation in Poland and in Ukraine, using the framework developed by Feldstein (1997, 1999).This approach stresses the fact that inflation increases distortions created by the tax system, in particular distortions to intertemporal saving decisions.We find that the effects are much smaller in the two transition countries than in developed marketeconomies.The reason is that taxation of investment returns is much more limited.Our results suggest that taxes on investment returns should be avoided in any future redesign of the tax system.
URN:NBN:fi:bof-201408072188
Keywords: 330